2019
DOI: 10.1055/s-0039-3400968
|View full text |Cite
|
Sign up to set email alerts
|

KISS1/KISS1R and Breast Cancer: Metastasis Promoter

Abstract: Kisspeptins (KPs), peptide products of the kisspeptin-1 (KISS1) gene, are the endogenous ligands for the KISS1 receptor, KISS1R, which is a G protein-coupled receptor. In many human tumors, KISS1 functions as a metastasis-suppressor gene and KISS1/KISS1R signaling has antimetastatic and tumor-suppressor roles. On the contrary, emerging evidence indicates that the KP/KISS1R pathway plays detrimental roles in triple negative breast cancer (TNBC), the most difficult type of breast cancer to treat. TNBC patients i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 101 publications
(128 reference statements)
0
12
0
Order By: Relevance
“…Kp regulate gonadotropin secretion in several mammalian species, acting via KISS1R. Numerous studies have delineated the antimetastatic and tumor-suppressant role of Kp/KISS1R signaling, which are found to inhibit nuclear factor kappa B (NF-kB) and mitogen-activated protein kinase (MAPK) signaling pathways [43][44][45][46][47][48]. We demonstrated the in vitro role of Kp via activation of its receptor, KISS1R, in regulating ASM proliferation and observed that cleaved forms of Kp, mainly Kp-10, alleviated PDGF-induced ASM proliferation by regulating the p38/MAPK signaling pathways [24].…”
Section: Discussionmentioning
confidence: 99%
“…Kp regulate gonadotropin secretion in several mammalian species, acting via KISS1R. Numerous studies have delineated the antimetastatic and tumor-suppressant role of Kp/KISS1R signaling, which are found to inhibit nuclear factor kappa B (NF-kB) and mitogen-activated protein kinase (MAPK) signaling pathways [43][44][45][46][47][48]. We demonstrated the in vitro role of Kp via activation of its receptor, KISS1R, in regulating ASM proliferation and observed that cleaved forms of Kp, mainly Kp-10, alleviated PDGF-induced ASM proliferation by regulating the p38/MAPK signaling pathways [24].…”
Section: Discussionmentioning
confidence: 99%
“…Our earlier work has shown that, in triple-negative breast cancer (TNBC), KISS1R signaling promotes tumor growth and metastasis ( 70 ). When ERα is reexpressed in TNBC cells, KISS1R is downregulated, demonstrating that ERα negatively regulates KISS1R expression in TNBC ( 85 ). In native TNBC cells lacking ERα, KISS1R signaling promotes epithelial-mesenchymal transition, MAPK activation, and cancer growth and invasion ( 70 , 86 88 ).…”
Section: Discussionmentioning
confidence: 99%
“…High expression levels of DNMT1 have been associated with silencing of NIS (51). The role of KISS1/KISS1R signaling is controversial in various types of cancers, as it has been associated with both roles in metastatic promotion and suppression (52)(53)(54). Savvidis et al found increased levels of KISS1 in extrathyroidal tissues of advanced differentiated TCs while an inverse correlation between KISS1R and tumor size (55).…”
Section: Dna Methylation In Thyroid Tumorsmentioning
confidence: 99%